2018
DOI: 10.1016/j.ejor.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Benders Decomposition based algorithm for an inventory location problem with stochastic inventory capacity constraints

Abstract: Ubeda (a)(b) , Pablo A. Miranda (a)(c) , Marco Macchi (b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…First, as this paper aims to contribute to the literature on the ILIP in the context of designing the low-carbon SCN with sustainable operations, we classify in Table 1.1 the published ILIP papers related to some critical features, such as the consideration of stochasticity, model formulation, inventory policy, and solution approach. A few recent studies proposed joint location-inventory models dealing with uncertain demand and revealed that optimizing both strategic location-allocation decisions and tactical inventory control decisions simultaneously can reduce the supply chain overall cost, and lead to optimal solutions (Puga & Tancrez, 2017;Shahabi et al, 2018;Tapia-Ubeda et al, 2018;Amiri-Aref et al, 2018). However, none of these works investigated the optimal location-inventory decisions with consideration of the low-carbon sustainability and the emission-compliance of the SCN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, as this paper aims to contribute to the literature on the ILIP in the context of designing the low-carbon SCN with sustainable operations, we classify in Table 1.1 the published ILIP papers related to some critical features, such as the consideration of stochasticity, model formulation, inventory policy, and solution approach. A few recent studies proposed joint location-inventory models dealing with uncertain demand and revealed that optimizing both strategic location-allocation decisions and tactical inventory control decisions simultaneously can reduce the supply chain overall cost, and lead to optimal solutions (Puga & Tancrez, 2017;Shahabi et al, 2018;Tapia-Ubeda et al, 2018;Amiri-Aref et al, 2018). However, none of these works investigated the optimal location-inventory decisions with consideration of the low-carbon sustainability and the emission-compliance of the SCN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the set of optimality cuts at iteration k can be written as shown in ( 11). It is worth to be mentioned that the proposed solution approach does not incorporates feasibility cuts by ensuring the feasibility of the SbP at each iteration by adding valid inequalities into the MP (see Tapia-Ubeda et al, 2018b). Notice that ,, DV  denotate fixed and known values for the SbP variables.…”
Section: Generalized Benders Decomposition-based Solution Approachmentioning
confidence: 99%
“…(s, Q), and then is not straight applicable to the general model introduced in this paper and in Tapia- Ubeda et al (2018a) . Thus, the proposed solution approach represents a generalization of the algorithm in Tapia- Ubeda et al (2018b), denoting a relevant contribution of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Tapia-Ubeda et al [40] studied an ILP for a supply chain consisting of two levels, with warehouses shipping product to customers. They developed a mixed integer nonlinear programming model to be solved using a Benders Decomposition algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%